Numerical Analysis of Horizontal Impact Resistance of Rock Socketed Pile with Steel Casing - Xiaolong Zhang; Lunliang Duan; Duoyin Wang (Advances in Civil Engineering)
Based on a Wharf project in Chongqing, this paper carries out experimental research and nonlinear finite element analysis on the impact resistance of steel casing rock socketed pile of inland river frame Wharf under horizontal impact load. The results show that the impact force and its growth rate, the bending moment of concrete pile core, and the maximum lateral displacement of pile top increase significantly with the increase of impact energy, and the linear increase of the maximum displacement of pile top is better. Under the same impact energy, with the increase of impact mass, the maximum impact force decreases, the maximum bending moment of concrete pile core and its vibration center value (platform value) increase, and the maximum displacement of pile top and its vibration center value (platform value) increase. Based on the impact mass m threshold, the criterion of different dynamic response forms of pile body is proposed. The impact mass threshold corresponds to the development of plastic hinge at the root of pile body. Through the parametric analysis method, it is obtained that the impact mass, impact velocity, and the maximum displacement of pile top meet the parabolic spherical relationship.